2-methoxyestradiol TPGS micelles attenuate cyclosporine A-induced nephrotoxicity in rats through inhibition of TGF-β1 and p-ERK1/2 axis - Al-Rabia, Mohammed W.; Alfaleh, Mohamed A.; Asfour, Hani Z.; Alharbi, Waleed S.; El-Moselhy, Mohamed A.; Alhakamy, Nabil A.; Fahmy, Usama A.; Ahmed, Osama A. A.; Fahmy, Omar; Rashad, Omar M.; Alamoudi, Abdulmohsin J.; Abdel-Naim, Ashraf (Multidisciplinary Digital Publishing Institute, 2022)
The immunosuppressant cyclosporine A (CSA) has been linked to serious renal toxic effects. Although 2-methoxyestradiol (2ME) possesses a wide range of pharmacological abilities, it suffers poor bioavailability after oral administration. The purpose of this study was to evaluate the potential of 2ME loaded D-ɑ-tocopheryl polyethylene glycol succinate (TPGS) micelles to prevent CSA-induced nephrotoxicity in rats. A 2ME-TPGS was prepared and showed particle size of 44.3 ± 3.5 nm with good entrapment efficiency and spherical structures. Male Wistar rats were divided into 5 groups, namely: Control, Vehicle, CSA, CSA + 2ME-Raw, and CSA + 2ME-Nano. CSA was injected daily at a SC dose of 20 mg/kg. Both 2ME-Raw and 2ME-Nano were given daily at oral doses of 5 mg/kg. Treatments continued for three successive weeks. 2ME-TPGS exerted significant protective effects against CSA nephrotoxicity. This was evidenced in ameliorating deterioration of renal functions, attenuation of pathological changes in kidney tissues, exerting significant anti-fibrotic, antioxidant, and anti-inflammatory effects together with significant anti-apoptotic effects. Western blot analyses showed both 2ME-Raw and 2ME-Nano significantly inhibited protein expression of TGF-β1 and phospho-ERK (p-ERK). It was observed that 2ME-TPGS, in almost all experiments, exerted superior protective effects as compared with 2ME-Raw. In conclusion, 2ME loaded in a TPGS nanocarrier possesses significant protective activities against CSA-induced kidney injury in rats. This is attributable to 2ME anti-fibrotic, antioxidant, anti-inflammatory, and anti-apoptotic activities which are mediated at least partly by inhibition of TGF-β1/p-ERK axis.